PELATIHAN PEMANFAATAN BARANG BEKAS MENJADI KERAJINAN TANGAN UNTUK MENINGKATKAN EKONOMI KREATIF DI KELURAHAN SARAE - Sri Ernawati, Muhammad Yusuf, Herry Nurdin, dan Jumharis (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Garbage is a problem that is quite difficult to handle in Indonesia, converting used goods into reusable goods can help reduce environmental pollution. Creativity in the use of used goods into handicrafts is a good enough solution to turn waste into useful items again, and even have a selling value. The purpose of this service is to provide training to the community, especially teenagers, to be creative in one of the new economic concepts that intensifies information and creativity and Human Resources (HR) as the most important production factor. Products produced from the creative economy are products that have characteristics, are unique, and are different from others. This community service activity is included in one of the work programs for Real Work Lectures (KKN) located in the Sarae village, Rasanae Barat sub-district, Bima City in 2020. The stages in this training activity are Program Socialization, Creative Class, Utilization of handicrafts and Evaluation. The result of this training activity is that the community, especially teenagers, develop their creativity and utilize that creativity to support the family economy and the environmental impact can be overcome.